S. K. Toka’s literary heritage in the collections of the National Archives of the Republic of Tuva - Mongush, Evgenii D. (The New Research of Tuva, 2020)
The literary heritage of Tuvan public and political figure, writer Salchak Kalbakhorekovich Toka is preserved at Tuva’s several archival institutions. This article deals with a small and relatively little known fond of manuscript versions of short stories and other fragments (11 archival units) preserved at the National Archives (prior to 07.04.2020 known as the State Archives) of the Republic of Tuva. Many fragments in these manuscripts radically differ from the later text in the printed version, which is important for studying the author’s evolution.The collection, for instance, contains the manuscript version of the short story “Wolf hunt” (1947). It was published in a collection in Russian in 1967, with important digressions from the Tuvan original: the protagonist now had a different name, and one of the supporting (but important) characters had had his occupation changed. As Toka was working in the text, the feelings became less expressive.S.K. Toka’s autobiographical trilogy “The word of the arat” was published in various versions, part by part, starting from 1932, and into the 1940s. As “The word of the arat”, it appeared in Russian in 1950, with some first editions in 1951 and 1964, and in Tuvan, in 1967. Both versions were many times reprinted. A comparative study of the fragments in the archival collection has revealed a number of cuts, additions and reworkings, with the manuscript version richer in vocabulary, minor details, descriptions and containing fewer ideological clichés.Comparing archival manuscripts and printed editions helps us trace the history of a literary text and sense changes in the author’s creative techniques, in evolution of his art. We can feel the minutest nuances of his work, which are so important for providing an objective interpretation of the author’s text – and yet are so fleeting and easy to neglect.
Keywords: State Archives of the Republic of Tuva; National Archives of the Republic of Tuva; Tuva; Salchak Kalbakhorekovich Toka; Tuvan literature